NUMERICAL SIMULATION RESEARCH ON THE ALUMINUM ALLOY THIN PLATE IMPACTED BY BLADE PROJECTILE - ZHANG TieCun; TIAN Lu; DENG YunFei; YE PeiZhi (Jixie qiangdu)
The simulation model of 2 mm thick 2 A12 aluminum alloy thin plate impacted by blade projectile was established by using the ABAQUS finite element software, including impact of yaw and oblique, and the yaw angle is 0-90° and the incidence angle is 0-60°. The effect of impact angle on the impact process, the ballistic limit of the target and the energy absorption of the target were investigated. The simulation results show that the target is mainly shear failure when the yaw angle is 0°, and a long plug and rectangular reaming are remained. When the yaw angle is 15°-60°, the failure mode of the target is ductile expansion and the hole area increases with the increase of the yaw angle. For the yaw angle ranges from 75° to 90°, the target is tore by tensile and the damage is serious. The failure mechanisms of target is both plug and petal damage when oblique impact. The ballistic limit of the target increases with the increase of the yaw angle, and the energy absorption of the target is related with the yaw angle and impact velocity of the projectile. The energy consumption of the target is not independent of the incidence angle.